Integrative multi-omics analysis of radionuclide-induced intestinal injury reveals the radioprotective role of L-citrulline through histone H3-mediated Cxcl3 - Ping Yang; Hao Bai; Tao Yan; Xiaopeng Xu; Xiaoyou Tang; Bin Song; Yulan Liu; Yunyun Lu; Pengfei Liu; Wenling Tu; Yuhong Shi; Shuyu Zhang (Journal of Translational Medicine)
Abstract Background The widespread application of nuclear technology has markedly heightened the risk of extensive, uncontrolled exposure to radiation. Nevertheless, in contrast to external irradiation, the biological impacts and countermeasures against internal irradiation from radionuclides remain inadequately characterized. Methods Mice were administered yttrium-90 (Y90) carbon microspheres via gavage at different dosages (0–5.0 mCi) to establish a radionuclides exposure model. A multi-omics analysis was employed to access alterations in gut microbiota, fecal and colonic metabolites profiles, and intestinal mRNA expression post-irradiation. The function of significant metabolite was validated at both cellular levels and organismal levels. Additionally, ChIP-Seq and RNA-Seq techniques were utilized to investigate the molecular mechanism underlying the actions of key metabolite. Results Exposure to Y90 resulted in intestinal damage and hematological impairment. Multi-omics analysis revealed significant alternations of gut microbiota, fecal metabolites, colonic metabolites, and intestinal mRNA expression following internal radiation exposure. Notably, L-citrulline was identified as a metabolite with changes observed in both fecal and colonic tissues, demonstrating radioprotective properties in vitro and in vivo. Mechanistically, L-citrulline facilitated the citrullination of histone H3 at the 17th site (H3Cit17), and multiple mRNAs including C-X-C motif chemokine ligand 3 (Cxcl3), were transcriptionally regulated by H3Cit17 post L-citrulline treatment. Furthermore, Cxcl3 conferred protective effects for intestinal epithelial cells against ionizing radiation. Conclusions The research offers critical perspectives on the intestinal and gut microbiota’s reaction to radionuclides exposure. It underscores the promise of L-citrulline as a radioprotective compound, which may have substantial ramifications for the formulation of strategies to mitigate radiation exposure.